The Role of Education in Fostering Entrepreneurial Spirit in the Young Generation - Said Ahmad, Muh. Ihsan; Idrus, Muhammad Ikram; Rijal, Syamsu (PT. LITERASI SAINS NUSANTARA, 2023)
Education has a very important role in shaping young people into competitive and innovative individuals, especially in the context of an increasingly complex and rapidly changing global economy. Entrepreneurial spirit is the ability of individuals to identify opportunities, take measured risks, and develop ideas into valuable innovations for society. This research aims to examine the role of education in encouraging the entrepreneurial spirit in the younger generation. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that the role of education in encouraging the entrepreneurial spirit in the younger generation is very important in facing challenges and rapid economic change. Education has the responsibility to provide relevant entrepreneurial skills, create a supportive environment, and remove the negative stigma towards failure. In addition, education should also reinforce ethical values and social responsibility and integrate technology to enhance learning effectiveness. Social entrepreneurship and inclusiveness should also be part of education to create positive social impact and equality of opportunity for all.